UPAYA MENINGKATKAN SELF ESTEEM SISWA KELAS VII DENGAN KONSELING TEKNIK COGNITIVE RESTRUCTURING BERBASIS MEDIA WHEEL - Febriana, Nina; Mahdina Munawarah; Muhammad Ayub; Ririanti Rachmayanie Jamain; Wahyu Adi Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of self-esteem degradation among adolescents in the digital era has become a crucial issue triggered by self-comparison habits on social media. Based on the Problem Checklist (DCM) assessment at SMP Negeri 4 Alalak, several seventh-grade students were identified as experiencing a crisis of self-confidence and self-worth. This study aims to improve students' self-esteem through group counseling services using the Cognitive Behavioral Therapy (CBT) approach with cognitive restructuring techniques integrated with the interactive media Wheel of Self-Esteem. The research method used was Guidance and Counseling Action Research (PTBK) adapting the Kemmis and McTaggart model, implemented in three cycles. The subjects consisted of 7 seventh-grade students purposively selected based on their low self-esteem levels. Data were collected using the Rosenberg Self-Esteem Scale (RSES). The results showed an increase in the average self-esteem score from 20.86 in the pre-test to 28.43 in the post-test. A non-parametric statistical analysis using the Wilcoxon signed-rank test obtained a p-value of 0.022 (p < 0.05), proving the improvement was significant. Qualitatively, students were able to identify negative thoughts and restructure them into coping thoughts. It is concluded that cognitive restructuring based on the Wheel of Self-Esteem is effective in improving students' self-esteem.